IMPROVING STUDENT LEARNING OUTCOMES USING IMAGE MEDIA IN ENGLISH LANGUAGE LEARNING IN CLASS XE1 SMAN 2 BUKIK BARISAN - Selvia Wilan Sari; Syahrul Syahrul; Wahyu Fitri (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
This research is motivated by improving student learning outcomes using image media. This study aims to determine student learning outcomes using learning media in English language learning class XE1 SMAN 2 Bukik Barisan. The method used by the researcher in this study was Class Action Research (PTK) with the subject of the study being Class XE1 consisting of 26 students. Average studying outcomes in cycle I is 74, however there was an average increase in cycle II, which was to 84. Learning outcomes in cycle I there is a studying completion of 69%, in cycle II there is an increase in learning completeness to 100%. After seeing the studying outcomes of students in cycle I and cycle II, the conclusion can be drawn, that is applying learning media in class XE1 SMAN 2 Kec.Bukik Barisan Academic Year 2022/2023 has increased student learning outcomes. It is hoped that teachers can apply Learning Media as an alternative and variety of teaching English in Class X SMA.